Authority of Land Procurement Committee In The Implementation of Compensation For Land Acquisition - M. Roesli; Asep Heri; Siti Rahayu (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2017)
The enactment of the Basic Agrarian Law in Indonesia creates dualism in land law that is sourced from customary law and on western law. The Basic Agrarian Law ends the dualism and creates the unification of our national land law. In the consideration of the Basic Agrarian Law it is stated that the need for a national agrarian law, based on customary law on land. In addition, article 5 of Basic Agrarian Law states that national land law is customary law; it indicates a functional relationship between customary law and national land law. In the development of national land law, customary law serves as a primary source in taking the necessary materials. Related to positive national law of land, customary law norms serve as complementary laws. In solving the problem, the author uses a sociological juridical problem approach to describe and analyze problems based on legal provisions and legal facts prevailing in the wider community. The results is then classified and material that can be used as to solve problems is determined .